PENATAAN RUANG DALAM RANGKA PELESTARIAN KAWASAN CAGAR BUDAYA: KAJIAN KOTA KUNO BANTEN LAMA - Yosua Adrian Pasaribu (Badan Riset dan Inovasi Nasional, 2019)
The old city of Banten Lama was an international port city developed in the 16-18th century AD. This old city, which once was the capital city of one of Indonesian Great Kingdom who has an ambassador in the Great Britain, can still be reconstructed based on the trace of monuments left scattered on the site at Kasemen District, Serang City. The preservation planning of this cultural heritage of an ancient city fits with the regional planning. Problems with this region heritage are the proximity between heritages and houses or shops and destructive activities. The data of spatial problems has never been mapped with a measured method. Spatial planning in this heritage area was done by aerial photography mapping. This paper reviews the use of the aerial photography method in planning for the preservation of space for cultural heritage areas. This method shows the existing condition of heritage buildings and sites that have proximity with houses, roads, and shops. This study shows that the preservation of the ancient city of Banten Lama can be done by providing substitutes for green open spaces for people who have been using cultural heritage sites for general recreational purposes, encouraging the development of settlements outside cultural heritage areas, and involving the community in community empowerment in the use of cultural heritage in harmony with preservation. Kota Kuno Banten Lama merupakan kota pelabuhan internasional yang berkembang pada abad 16-18 M. Ibu kota kerajaan tradisional Indonesia yang memiliki duta besar di Inggris ini masih dapat direkonstruksi berdasarkan monumen-monumen yang tersebar di wilayah Kecamatan Kasemen, Kota Serang. Pelestarian kawasan kota kuno bersinggungan dengan penataan ruang di wilayah tersebut. Permasalahan dalam pelestarian situs dan bangunan cagar budaya di Banten adalah kedekatan jarak antara cagar budaya dengan permukiman atau pertokoan dan pemanfaatan yang tidak selaras dengan pelestarian. Data permasalahan keruangan tersebut belum pernah dipetakan dengan metode yang terukur. Tulisan ini mengulas mengenai penggunaan metode foto udara dalam perencanaan pelestarian ruang kawasan cagar budaya. Metode tersebut dapat memperlihatkan kondisi eksisting situs dan bangunan cagar budaya yang bersinggungan dengan permukiman, jalan, dan pertokoan. Kajian menunjukkan bahwa pelestarian kota kuno Banten Lama dapat dilakukan dengan menyediakan pengganti lapangan terbuka hijau bagi masyarakat yang selama ini menggunakan situs-situs cagar budaya sebagai sarana rekreasi umum, mendorong pembangunan permukiman di luar kawasan cagar budaya, dan melibatkan masyarakat dalam pemanfaatan cagar budaya yang selaras dengan pelestarian.